2016
DOI: 10.1002/app.43440
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic acrylate copolymer fatliquor for ecological leather: Influence of molecular weight on performances

Abstract: With increasing demand for ecological leather, ecological fatliquors with good comprehensive properties are getting more and more attention. The amphiphilic acrylate copolymer containing both hydrophilic (carboxyl) and hydrophobic (long alkyl) groups is one of the main alternatives to conventional fatliquors. In this paper, a series of poly(acrylic acid-co-stearyl acrylate) with different relative molecular weights were prepared, and the influence of the molecular weight on their application performances were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Meanwhile, when the number average molecular weight of amphiphilic acrylate copolymer fatliquor is within 9000–15,000, the copolymer has good permeability and absorptive capacity. It will further endow leather with excellent physical and mechanical properties 50 …”
Section: Application Of Amphoteric Materials In Leathermentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, when the number average molecular weight of amphiphilic acrylate copolymer fatliquor is within 9000–15,000, the copolymer has good permeability and absorptive capacity. It will further endow leather with excellent physical and mechanical properties 50 …”
Section: Application Of Amphoteric Materials In Leathermentioning
confidence: 99%
“… (A) Chemical structure of amphiphilic acrylate copolymer fatliquor; (B) Penetration of five copolymers and conventional sulfonated rapeseed oil fatliquor (Dowellor SS); (C) Physical and mechanical properties of fatliquored leathers. Reprinted with permission from Reference 50. Copyright 2016, Wiley, Periodicals, Inc…”
Section: Application Of Amphoteric Materials In Leathermentioning
confidence: 99%
“…Bio-based natural animal fats and vegetable oils are widely employed as natural oils to prepare fatliquors. Various functional groups, such as hydroxy, carboxyl, amino, sulfonic acid, and phosphoric acid groups, have been introduced into the molecular chain of animal fats and vegetable oils by a chemical modification method, which can not only improve the molecular weight of the fatliquors but also increase the intermolecular interaction strength with the leather collagen, thus reducing the fogging phenomenon in a high-temperature environment. , In the work reported by Yu et al, jatropha oil was epoxidized, esterified, and co-polymerized via a three-step process to introduce reactive −COOH and −OH groups, which formed strong interactions with the −NH 2 groups of the leather collagen. Although the leather fatliquored with jatropha oil-based fatliquors exhibited a significantly lower fogging value (0.89 mg), the chemical modification process was complicated, and the structure–property relationship between the chemical structure of the fatliquors and the fogging value of the fatliquored leather was not clear.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that many polymers, after coating, may improve important characteristics of pristine leather like the flexibility and water‐vapor permeability . It was recognized that methacrylic polymers can be conveniently used for leather modification to improve mechanical properties or durability without compromising on unique advantageous characteristics of leather . The photo‐oxidative stability of most of the methacrylic polymers is fairly high, which can also be tuned by incorporating various functional groups .…”
Section: Introductionmentioning
confidence: 99%